ENHANCING STUDENTS’ SKILL IN SPEAKING NARRATIVE BY USING PICTURE SERIES - Fitra Murni Ar (English Language Teaching and Research, 2018)
Although the students have sufficient knowledge in grammar and vocabulary, they still are afraid of speaking. They still have a lot of mistakes in speaking, especially narrative.This classroom action research was done to see the enhancement of students’ skill in speaking narrative by using picture series. The research was conducted at the second year science class 1(XI IA 1) of SMAN 3 Padang Panjang in the 2017/ 2018 academic year. It was done in two cycles. The data were collected through pre-test, formative test and observation. The students were led to tell the stories by using picture series, and then they were guided to tell the stories well. Through observation and formative test, it seemed that the students liked and enjoyed speaking narrative. It could be seen from their achievement improved from cycle to cycle and from their test results. In conclusion, the students’ speaking ability can be improved if they know what and how to speak, and the use of the appropriate teaching media is very important. One of teaching aids that can be used to enhance students’ ability in speaking narrative is picture series. It is suggested to English teachers to use picture series in teaching speaking narrative. Keywords : speaking, narrative, picture series